Partisipatori Desain dalam Strategi Pengembangan Desain Produk Pandan dengan Menggabungkan Anyaman Pandan dan Kulit Sintetis untuk Memajukan Industri Kreatif - Kendall Malik; Ferry Fernando; Yandri; Novia Murni; Ramadhani Kurniawan; Hanafi Malik (Besaung : Jurnal Seni Desain dan Budaya, 2026)
This study examines participatory design as a strategy for developing pandan craft products by combining woven pandan and synthetic leather to advance the local creative industry in Nagari Padang Laweh Selatan, Sijunjung. The research is motivated by the limited design variation, finishing quality, and market competitiveness of traditional pandan products produced by Kelompok Wanita Tani Sejahtera Sijunjung. This study aims to describe the participatory design process, analyze the potential of material combination, and formulate product development strategies rooted in local knowledge and market needs. A qualitative case study method was applied through observation, semi-structured interviews, focus group discussions, visual documentation, and design experiments. The results show that the integration of woven pandan and synthetic leather can improve product structure, visual quality, functional value, and contemporary appeal while maintaining local identity. Several product prototype s, including bags, wallets, keychains, and coasters, were developed through collaborative exploration between artisans, researchers, designers, business actors, and prospective consumers. The findings indicate that participatory design strengthens artisans’ involvement, encourages knowledge exchange, and supports more realistic and sustainable product innovation. The study concludes that participatory design is an effective approach for empowering women artisans, increasing product value, and supporting community-based creative industry development